Physical attractiveness and sex as modulatory factors of empathic brain responses to pain - Siuda, Kamila J.; Rymarczyk, Krystyna; Żurawski, Łukasz; Jednoróg, Katarzyna; Marchewka, Artur (Frontiers in Behavioral Neuroscience, 2015)
Empathy is a process that comprises affective sharing, imagining, and understanding the emotions and mental states of others. The brain structures involved in empathy for physical pain include the anterior insula (AI), and the anterior cingulate cortex (ACC). High empathy may lead people to undertake pro-social behavior. It is important to understand how this process can be changed, and what factors these empathic responses depend on. Physical attractiveness is a major social and evolutional cue, playing a role in the formation of interpersonal evaluation. The aim of the study was to determine how attractiveness affects the level of empathy both in relation to self-rated behavior and in terms of activation of specific empathy-related brain regions. Twenty-seven subjects (14 female and 13 male) were studied using functional magnetic resonance imaging (fMRI) method while they were watching short video scenes involving physically more and less attractive men and women who exhibited pain responses. In the absence of behavioral effects in compassion ratings, we observed stronger activation in empathic brain structures (ACC; AI) for less attractive men and for attractive women than for attractive men. Evolutionary psychology studies suggest that beauty is valued more highly in females than males, which might lead observers to empathize more strongly with the attractive woman than the men. Attractive mens’ faces are typically associated with enhanced masculine facial characteristics and are considered to possess fewer desirable personality traits compared with feminized faces. This could explain why more empathy was shown to less attractive men. In conclusion, the study showed that the attractiveness and sex of a model are important modulators of empathy for pain.